Sistem pembayaran QRIS sebagai upaya pengembangan UMKM di kota Ambon - Gainau, Paskanova Christi; Engko, Cecilia; Gaspersz, Yesica Thelma (Journal of Business & Banking, 2023)
This study aims to examine the effect of using the QRIS payment system on MSME development in Ambon City through Theory of Acceptance Model. It uses the sample from all MSME culinary delights in Ambon City, taken based on the determined criteria such as meeting the criteria are 45 SMEs. The data were analyzed using multiple linear regression, which was processed by the SPSS version 21. The result shows that partially Perceived Usefulness and Perceived ease of use have a significant influence on the development of MSMEs in Ambon City. The more useful QRIS is, the more MSMEs will develop, as well as the easier it is to use QRIS, so it will be easy for business actors to adapt and their businesses will develop. It practically implies that MSMEs in Ambon City are getting more and more aware that the perceived usefulness and perceived ease of use available in the QRIS are able to encourage business development. Apart from that, Bank Indonesia as the promoter of QRIS implementation for MSMEs needs to monitor entrepreneurs using QRIS so that they can answer any obstacles they still face. Theoretically, it also implies that this research provides a new area of research not only limited to interest in using it but directly towards the application of new technology and its influence on the development of MSMEs.